2010
DOI: 10.1111/j.1532-7795.2010.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Identity Formation of American Indian Adolescents: Local, National, and Global Considerations

Abstract: A conceptual model is presented that approaches identity formation of American Indian adolescents according to 3 levels of social contextual influenceFlocal, national, and globalFrelative to types of identity, dynamics of identity, and sources of influence. Ethnic identity of American Indians is embedded within the local cultural milieu and encompasses an array of dimensions organized around identification, connection, and culture/spirituality. The national or societal level brings additional complexities acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 82 publications
(114 reference statements)
0
44
0
Order By: Relevance
“…Potential explanations for this finding may include the complexity in measuring ethnic identity and the social norms of use within Native American and Multiracial communities. For example, Markstrom (2011) proposed a multifaceted model for Native American ethnic identity that include domains outside of those measured by the MEIM, such as connection to land and spirituality. Additionally, when the overall construct of ethnic identity has been disaggregated, differing effects on drug outcomes have been found, such that Native Americans with a stronger sense of ethnic pride displayed more antidrug attitudes while ethnic behavior was unrelated to attitudes towards drugs (Kulis, Napoli, Marsiglia, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Potential explanations for this finding may include the complexity in measuring ethnic identity and the social norms of use within Native American and Multiracial communities. For example, Markstrom (2011) proposed a multifaceted model for Native American ethnic identity that include domains outside of those measured by the MEIM, such as connection to land and spirituality. Additionally, when the overall construct of ethnic identity has been disaggregated, differing effects on drug outcomes have been found, such that Native Americans with a stronger sense of ethnic pride displayed more antidrug attitudes while ethnic behavior was unrelated to attitudes towards drugs (Kulis, Napoli, Marsiglia, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It was also found to be important for identity development and wellbeing that they could transfer the identity aspects they explored and developed online to offline contexts (Crowson and Goulding 2013;DeHaan et al 2012). In the reviewed research that concern ethnic minorities, it was argued that online contexts may strengthen individuals' ethnic identity by making contexts beyond the offline environment available (Markstrom 2011). The research showed that individuals in ethnic minorities tended to emphasize cultural aspects in their online self-presentations (Grasmuck et al 2009).…”
Section: Opportunities For Identity Explorations: Aspects Of Identitymentioning
confidence: 98%
“…In general, the Internet can reinforce ethnic identity by providing bridges beyond the local community. Markstrom (2010), for example, argues that the Internet can provide information and prompt action to address common concerns among American Indian adolescents, as well as involve the adolescents in e-commerce of culturally based craft products. Some individuals use Facebook to express ethnic identity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That is, adolescents can join “groups” reflecting aspects of their identity that they wish to explore or deepen and thereby foster a group identity. Relatedly, adolescents can explore and expand their ideas and interests into new arenas through the Internet, e.g., communicating with others from more diverse backgrounds and expanding into new intellectual, political, and social networks that create opportunities for transnational and global connections (Markstrom, 2010). Such connections can broaden as well as deepen self-identity while, at the same time, enhance feelings of belongingness and affiliation.…”
Section: Introductionmentioning
confidence: 99%